Evaluation of apoptosis in nasal and buccal cells of septic patients. - Vassiliou, Stavros; Yapijakis, Christos; Derka, Spyridoula; Papakosta, Veronica; Psyrri, Amanda; Antonakis, Pantelis; Goutzanis, Lambros; Konstadoulakis, Manousos; George Androulakis; Vairaktaris, Eleftherios (In Vivo, 2007)
BACKGROUND: Inhibition of lung cell apoptosis in the bronchoalveolar lavage (BAL) of septic patients may have a prognostic value for the severity of sepsis. The present study evaluated apoptosis in the nasal and buccal mucosa of septic patients as an alternative and less invasive approach for studying the cells involved in bronchial inflammation. PATIENTS AND METHODS: A prospective study was designed. Nasal and buccal mucosa brushings were obtained from 20 consecutive septic patients who were admitted to two intensive care units. Twenty-four patients scheduled to undergo surgery for colorectal cancer or laparascopic cholocystectomy were the control group. Apoptosis was evaluated using a TUNEL assay, while BCL-2 and BAX expression were evaluated by immunohistochemistry. RESULTS: Significantly reduced apoptosis in the nasal mucosa of septic patients compared to the control group (p=0.043) was detected only by the TUNEL assay. CONCLUSION: Reduced apoptosis was found during sepsis in the nasal mucosa in accordance with the reduced apoptosis in the lungs of septic patients. In contrast to septic lungs the underlying mechanism leading to apoptosis in the nasal mucosa was unrelated to the expression of two apoptosis-related genes BCL-2 and BAX.
Keywords: Aged; Aged, 80 and over; apoptosis; Cheek; Female; Humans; Male; Middle Aged; Nasal Mucosa; Nose; Proto-Oncogene Proteins c-bcl-2; Sepsis